Metode Edukasi Brainstorming dan Edukasi Buzz Group Terhadap Peningkatan Self Care pada Klien Congestive Heart Failure - Eka Yudha Chrisanto; Andoko Andoko; Cindy Desmonika (Universitas Malahayati Lampung, 2022)
ABSTRACT: BRAINSTORMING EDUCATION AND BUZZ GROUP EDUCATION METHODS TO IMPROVING SELF CARE IN CONGESTIVE HEART FAILURE CLIENTS Introduction: Congestive heart failure is a serious disease, with the incidence and number of patients undergoing rehospitalization that continues to increase. This condition is caused by the lack of knowledge of clients and families about congestive heart failure and self care at home. Brainstorming education and Buzz group education can increase clients' understanding of Self Care.Objective: This study aims to analyze the effectiveness of the Brainstorming educational method and the Buzz Group educational method on Self Care in patients with Congestive Heart Failure at Harapan Bunda Hospital in 2020.Methods: This research is a Quasi Experiment research using a pretest and posttest design. The study population was clients who were treated at Harapan Bunda Hospital in 2020. The sample was taken using purposive sampling consisting of two groups, namely the brainstorming group of 15 respondents and the buzz group of 15 respondents.Results: The results showed that there was a difference in the average value of increasing self-care before and after giving education using the brainstorming method with a difference in the mean value of 6.20 and the difference in increasing self-care before and after giving education using the buzz group method, which was 21.8. While the results of the analysis of differences in self care using the brainstorming and buzz group education methods with an average self-care value of 49.40 and 67.47, respectively, which means that the buzz group has a higher average value than the brainstorming group. The results of the independent t-test obtained a p-value of 0.000.Conclusion: The buzz group method is more effective in improving self-care in patients with Congestive Heart Failure compared to the brainstorming educational method. It is recommended that Harapan Bunda Hospital can use varied methods such as buzz groups in providing self-care education to Congestive Heart Failure patients. Keywords : Brainstorming, Buzz Group, Self Care, Congestive Heart Failure INTISARI: METODE EDUKASI BRAINSTORMING DAN EDUKASI BUZZ GROUP TERHADAP PENINGKATAN SELF CARE PADA KLIEN CONGESTIVE HEART FAILURE Pendahuluan: Congestive heart failure merupakan penyakit yang cukup serius, dengan angka kejadian dan jumlah pasien untuk mengalami rehospitalisasi yang terus meningkat.Kondisi ini dikarenkan minimnya pengetahuan klien dan keluarga tentang penyakit congestive heart failure dan self care di rumah. Edukasi brainstroming dan edukasi Buzz group dapat meningkatkan pemahaman Self Care klien.Tujuan: Penelitian ini bertujuan untuk menganalisis efektifitas metode edukasi Brainstorming dan metode edukasi Buzz Group terhadap Self Care pada pasien penderita Congestive Heart Failure di Rumah Sakit Harapan Bunda Tahun 2020.Metode: Penelitian ini merupakan penelitian Quasi Experiment dengan menggunakan rancangan pretest and posttest design. Populasi penelitian adalah klien yang dirawat di Rumah Sakit Harapan Bunda pada Tahun 2020. Sampel diambil dengan menggunakan purposive sampling yang terdiri dari dua kelompok, yaitu kelompok brainstorming sebanyak 15 responden dan kelompok buzz group sebanyak 15 responden.Hasil: Hasil penelitian menunjukan terdapat perbedaan nilai rata-rata peningkatan self care sebelum dan sesudah pemberian edukasi menggunakan metode brainstorming dengan selisih nilai mean 6,20 dan perbedaan peningkatan self care sebelum dan sesudah pemberian edukasi menggunakan metode buzz group yaitu 21,8. Sedangkan hasil analisis perbedaan self care menggunakan metode edukasi brainstorming dan buzz group dengan nilai rata-rata self care masing-masing 49,40 dan 67,47 yang artinya pada kelompok buzz group memiliki nilai rata-rata lebih tinggi dibandingkan kelompok brainstorming. Hasil uji t-tes independen didapat nilai p-value 0,000 .Kesimpulan: Metode buzz group lebih efektif dalam peningkatan self care pada pasien penderita Congestive Heart Failure dibandingkan dengan metode edukasi brainstorming. Kata Kunci : Congestive Heart Failure, Brainstorming, Buzz Group, Self Care